2012
DOI: 10.1128/mbio.00251-12
|View full text |Cite
|
Sign up to set email alerts
|

Serial Analysis of the Gut and Respiratory Microbiome in Cystic Fibrosis in Infancy: Interaction between Intestinal and Respiratory Tracts and Impact of Nutritional Exposures

Abstract: Pulmonary damage caused by chronic colonization of the cystic fibrosis (CF) lung by microbial communities is the proximal cause of respiratory failure. While there has been an effort to document the microbiome of the CF lung in pediatric and adult patients, little is known regarding the developing microflora in infants. We examined the respiratory and intestinal microbiota development in infants with CF from birth to 21 months. Distinct genera dominated in the gut compared to those in the respiratory tract, ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
294
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(326 citation statements)
references
References 54 publications
10
294
1
6
Order By: Relevance
“…Their increased residence time allows anaerobes to degrade respiratory mucins and condition the lung environment into a niche that is suitable for pathogens to thrive (Fig 8C). Several lines of clinical evidence exist in support of our proposed model: (i) pediatric patients often have asymptomatic primary colonization by oral anaerobes [45,46] prior to the establishment of chronic P. aeruginosa infections, (ii) routine administration of broad-spectrum antibiotics in the absence of respiratory infection symptoms is an effective therapy to delay the onset of colonization by P. aeruginosa and reduce the frequency of acute exacerbations [47,48], and (iii) the in vitro antibiotic susceptibility of lung pathogens does not always correlate with clinical outcomes [49]. In the latter instance, we propose that antibiotics do not solely target the pathogen, but rather disrupt the complex metabolic interactions that supply them with substrates for growth and stimulate their pathogenicity.…”
Section: Discussionmentioning
confidence: 93%
“…Their increased residence time allows anaerobes to degrade respiratory mucins and condition the lung environment into a niche that is suitable for pathogens to thrive (Fig 8C). Several lines of clinical evidence exist in support of our proposed model: (i) pediatric patients often have asymptomatic primary colonization by oral anaerobes [45,46] prior to the establishment of chronic P. aeruginosa infections, (ii) routine administration of broad-spectrum antibiotics in the absence of respiratory infection symptoms is an effective therapy to delay the onset of colonization by P. aeruginosa and reduce the frequency of acute exacerbations [47,48], and (iii) the in vitro antibiotic susceptibility of lung pathogens does not always correlate with clinical outcomes [49]. In the latter instance, we propose that antibiotics do not solely target the pathogen, but rather disrupt the complex metabolic interactions that supply them with substrates for growth and stimulate their pathogenicity.…”
Section: Discussionmentioning
confidence: 93%
“…Limited studies of children with CF indicate that bacterial community diversity (a measure of both the number and relative abundances of the species present) increases with age (14,26). In contrast, several cross-sectional and longitudinal studies of adults have shown that diversity decreases with age and declining lung function (14,18,22,23).…”
Section: The Lung Microbiome In Cfmentioning
confidence: 99%
“…The low bacterial diversity found in CF has been associated with higher inflammation, more advanced disease stage, and worse prognosis (83,84). Dietary manipulations could restore microbial diversity in the airways in CF (85). Furthermore, low microbiota diversity also precedes the development of an exacerbation (86).…”
Section: Lessons Learned From the Study Of Airway Microbiota In Lungmentioning
confidence: 99%